Impact of the Digital Economy on Carbon Intensity: -- Empirical Analysis based on Heterogeneity and Moderating Effects - Liu, Shiyao (Transactions on Economics, Business and Management Research, 2023)
Under the background of "dual-carbon" target, digital economy, as a rapidly developing economic form, can play a certain role in promoting carbon emission reduction. This paper utilizes the panel data of 30 provinces in China from 2012 to 2020 to empirically investigate the impact of digital economy on carbon emission intensity. The empirical results show that the digital economy has a significant inhibitory effect on carbon emission intensity; the heterogeneity analysis shows that the inhibitory effect of the digital economy on carbon emission intensity is more significant in the central region, the region with a lower level of green carbon sinks, and the region with a higher level of development of digital infrastructure; and the analysis of the moderating effect shows that the level of industrialization and the degree of government intervention have a negative and positive moderating effect, respectively, on the inhibitory effect of the digital economy on carbon emission intensity. The analysis of the regulating effect shows that the level of industrialization and the degree of government intervention have negative and positive regulating effects on the digital economy's suppression of carbon emission intensity, respectively. Therefore, we should vigorously develop the digital economy, strengthen the construction of digital infrastructure, and promote the digital economy to play the role of carbon emission reduction.